Crop Water Productivity in Semi-arid Regions: From Field to Large Scales - De, Antonio H; Teixeira, C; Bassoi, Luis H (Annals of Arid Zone, 2016)
The semi-arid regions of the world are marked by socio-economic disparities and environmental vulnerabilities. Water managers in river basins are faced with several challenges, such as competition among different water user groups, local over-exploitation of aquifers, climate and land use changes, non-source pollution, erosion, and sedimentation. Water policy makers have to work out strategies for integrated water management, which rely on a proper knowledge based on the physical conditions encountered in the river basins. The intensification of the land use change implies a necessity of a better knowledge of the water use and food production to improve crop water productivity for rational water resources planning. This paper presents an overview of the key concepts involved in water productivity analyses from field to regional scales in areas with quick land use change, with some examples in the semi-arid region in the Northeast Brazil. It is emphasized the use’ of tools for estimating spatially distributed water related variables to describe the water cycle in irrigated agriculture under semi-arid conditions. Moreover, they can beÂ· operationally impleqtented to monitor the intensification of agriculture avoiding the adverse impC’ct on downstream water users. Conclusions and recommendations are given to improve the evaluation of irrigation in large areas in terms of crop water ptbductivity and their impacts on water resources, by the intensification of irrigated agriculture in semi-arid regions. Key words: Evapotranspiration, biomass production, remote sensing, energy balance, irrigation, water resources.